Morbidities and follow-up of admitted late preterm infants - Ramya, Bandi; Kumar G.R, Basanth; G., Guruprasad (International Journal of Contemporary Pediatrics, 2016)
Background: The objective of the study was to document the neonatal morbidities in late preterm infants admitted to tertiary care newborn centre. Methods: Observational prospective case series study. All late preterm infants during the study period of one year were included. Descriptive statistics and analysis of the morbidities was done. A follow up of 6 months was done to assess growth and development. Results: 100 infants were studied. The admission complaints were respiratory distress (32%), low birth weight care (31%), jaundice (15%), feeding difficulties & lethargy (5%). morbidities included jaundice (68%), hypoglycaemia (38%), septicaemia (24%), respiratory distress syndrome (20%) & transient tachypnea of newborn (15%). 55% of infants with subnormal head growth were identified in follow-up. Conclusions: The most common cause for admission was respiratory distress (32%) within 48 hours of life and jaundice later. Most common morbidity was jaundice (68%).Most of the morbidities could be effectively treated with timely care. Follow up of these infants for early identification and treatment of problems is imperative.